Analysis of Bantul Regency Regional Regulation Number 5 of 2020 concerning Pamong Kalurahan - Sasmita Alya Hestina; Vicki Dwi Purnomo; Syukron Abdul Kadir; Benedictus Hestu Cipto Handoyo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The village head is assisted by village officials, to carry out their roles and functions in building and administering village government. The politicization in the preparation of the formation of the Bantul Regency Regional Regulation Number 5 of 2020 Concerning Pamong Kalurahan is a study of the Governor of the Special Region of Yogyakarta Regulation Number 25 of 2019 concerning Guidelines for Institutional Privileges Affairs in Regency/City and Kalurahan Governments. Regional regulations are one of the legal products, so the principles for their formation, application and enforcement must contain legal values in general, in the formation of the Bantul Regency Regional Regulation Number 5 of 2020 concerning Pamong Kalurahan.